Magnetic resonance imaging in dogs with neuroangiostrongyliasis (rat lungworm disease). Issue 2 (21st February 2021) - Wun, Matthew K.; Malik, Richard; Yu, Jane; Chow, Kathleen E.; Lau, Michelle; Podadera, Juan M.; Webster, Natalie; Lee, Rogan; Šlapeta, Jan; Davies, Sarah
Abstract: The magnetic resonance imaging (MRI) appearance of the brain and spinal cord in humans with neuroangiostrongyliasis (NA) due to Angiostrongylus cantonensis infection has been well reported. Equivalent studies in animals are lacking. This case series describes clinical and MRI findings in 11 dogs with presumptively or definitively diagnosed NA. MRI of the brain and/or spinal cord was performed using high-field (1.5 T) or low-field (0.25 T) scanners using various combinations of transverse, sagittal, dorsal and three-dimensional (3D) T1-weighted (T1W), transverse, sagittal and dorsal T2-weighted (T2W), T2W fluid-attenuated inversion recovery (FLAIR) and T2*-weighted (T2*W) gradient echo (GRE), dorsal T2W short tau inversion recovery (STIR) and post-gadolinium transverse, sagittal, dorsal and 3D T1W and transverse T2W FLAIR sequences. In 4/6 cases where the brain was imaged, changes consistent with diffuse meningoencephalitis were observed. Evidence of meningeal involvement was evident even when not clinically apparent. The spinal cord was imaged in 9 dogs, with evidence of meningitis and myelitis detected in regions consistent with the observed neuroanatomical localization. Pathognomonic changes of neural larva migrans, as described in some human patients with NA, were not detected. NA should be considered in the differential diagnosis of dogs with MRI evidence of focal or diffuse meningitis, myelitis and/or encephalitis, especially in areas where A. cantonensis is endemic. If not precluded by imaging findings suggestive of brain herniation, cerebrospinal fluid (CSF) collection for cytology, fluid analysis, real-time polymerase chain reaction (qPCR) and enzyme-linked immunosorbent assay (ELISA) testing should be considered mandatory in such cases after the MRI studies.